Structural aspects of metamagnetism in Ca_{2-x}Sr_{x}RuO_4 (0.2 < x < 0.5): field tuning of orbital occupation - Kriener, M; Steffens, P; Baier, J; Schumann, O; Zabel, T; Lorenz, T; Friedt, O; Mueller, R; Gukasov, A; Radaelli, P; Reutler, P; Revcolevschi, A; et al. (2004)
The crystal structure of Ca_{2-x}Sr_xRuO_4 with 0.2 < x < 1.0 has been studied by diffraction techniques and by high resolution capacitance dilatometry as a function of temperature and magnetic field. Upon cooling in zero magnetic field below about 25 K the structure shrinks along the c-direction and elongates in the a, b planes (0.2 < x < 1.0), whereas the opposite occurs upon cooling at high-field (x = 0.2 and 0.5). These findings indicate an orbital rearrangement driven by temperature and magnetic field, which accompanies the metamagnetic transition in these compounds.